Insights into heart-tumor interactions in heart failure - Caller, Tal; Moore, Kathryn J.; Lehmann, Lorenz; Wu, Sean M.; Leor, Jonathan (Circulation research, 2025)
Heart failure (HF) often coexists with cancer. Beyond the known cardiotoxicity of some cancer treatments, HF itself has been associated with increased cancer incidence. The 2 conditions share common risk factors, mechanisms, and interactions that can worsen patient outcomes. The bidirectional relationship between HF and cancer presents a complex interplay of factors that are not fully understood. Recent preclinical evidence suggests that HF may promote tumor growth via the release of protumorigenic factors from the injured heart, revealing HF as a potentially protumorigenic condition. Our review discusses the biological crosstalk between HF and cancer, emphasizing the impact of HF on tumor growth, with inflammation, and modulating the immune system as central mechanisms. We further explore the clinical implications of this connection and propose future research directions. Understanding the mechanistic overlap and interactions between HF and cancer could lead to new biomarkers and therapies, addressing the growing prevalence of both conditions and enhancing approaches to diagnosis, prevention, and treatment.
Online veröffentlicht: 22. Mai 2025
Gesehen am 03.09.2025